1999
DOI: 10.1111/j.1600-0625.1999.tb00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin: a review

Abstract: Neopterin was discovered in bee larvae, in worker bees and in Amsterdam, The Netherlands royal jelly. The compound was termed ''neopterin'' to denote that it might start a new (Greek, neo) epoch in pteridine research. Increased concentrations of neopterin were reported in patients with viral infections, suggesting that increased neopterin may originate from the immune response of patients to the infections. In vitro studies revealed that human monocytes/macrophages produce neopterin when stimulated by interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 69 publications
3
126
1
2
Order By: Relevance
“…In 7.8% of cases the serum neopterin level was above this limit (12). Comparable results were achieved by Hammerlinck who estimated the serum neopterin normal level to be 10.5 nmol/L in 99% of 1837 healthy adults (7). Lower cut-off value of 8.7 nmol/L (= 95th percentile) was the result of Schennach studies in 1156 healthy blood donors.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In 7.8% of cases the serum neopterin level was above this limit (12). Comparable results were achieved by Hammerlinck who estimated the serum neopterin normal level to be 10.5 nmol/L in 99% of 1837 healthy adults (7). Lower cut-off value of 8.7 nmol/L (= 95th percentile) was the result of Schennach studies in 1156 healthy blood donors.…”
Section: Discussionsupporting
confidence: 49%
“…The body temperature was normal in all the patients. Children which had been vaccinated or had received the antibiotics therapy during the previous 4 weeks were excluded from the study (7,8). Children with body weight below third percentile for height did not enter the study either, as protein-caloric malnutrition may compromise cellular immunity.…”
Section: Methodsmentioning
confidence: 99%
“…Original Article Eur J Gen Med 2015; 12(1):1-6 DOI : 10.15197/sabad.1.12.01 Eur J Gen Med 2015; 12(1): [1][2][3][4][5][6] Neopterin in chronic HBV and HCV 2 hepatitis, HIV-hepatitis D co-infection, hepatocellular carcinoma, malignity, immunosuppressive condition and cirrhosis was considered as an exclusion criterion.…”
Section: Neopterin (Np) Is a Pteridine Derivative That Is Secreted Asmentioning
confidence: 99%
“…The purpose in this study was to investigate the relationship between the NP levels and the disease and determining the efficacy of an interferon (IFN) therapy in patients with chronic hepatitis B (CHB) and C (CHC).Original Article Eur J Gen Med 2015; 12(1):1-6 DOI : 10.15197/sabad.1.12.01 Eur J Gen Med 2015; 12(1): [1][2][3][4][5][6] Neopterin in chronic HBV and HCV 2 hepatitis, HIV-hepatitis D co-infection, hepatocellular carcinoma, malignity, immunosuppressive condition and cirrhosis was considered as an exclusion criterion.Written consents of the patients and approval of the ethics committee were obtained for the study. Patient blood samples were taken on the day of biopsy from the patients who were included in the study, at the beginning and end of the treatment from the patients who were administered an IFN therapy and at the time of enrollment from the healthy individuals in the control group.…”
mentioning
confidence: 99%
“…Neopterin was dissolved in 1N HCl at 1 mg/mL and diluted tenfold with Dulbecco's phosphatebuffered saline (PBS). Hamerlinck reported that the concentration of neopterin is 5.89±1.78 nM in normal human serum (19). Murr et al showed that the mean serum neopterin level in patients with serious infection by Streptococcus pyogenes is 152 nM (range, 71-242 nM) (12).…”
Section: Micementioning
confidence: 99%